Die Berücksichtigung privater Nutzen und Kosten bei der Bewertung von Verkehrssicherheitsmaßnahmen - Willeke, Rainer 1924-2018; Lewen, Franz-Josef (1988)
Benefits and costs associated with specific traffic safety measures: highway advisory radio (Autonotfunk-System), children's traffic safety clubs (Kinder-Verkehrs-Club), traffic restraint (Verkehrsberuhigung).
Keywords: Highway communications -- Germany (West) -- Cost effectiveness; Public safety radio service -- Germany (West) -- Cost effectiveness; Traffic safety and children -- Germany (West) -- Cost effectiveness; Traffic safety -- Cost effectiveness; Verkehrssicherheit; Kosten-Nutzen-Analyse